Development of a low-cost, simple, fast and quantitative lateral-flow immunochromatographic assay (ICA) strip for melatonin in health foods. Issue 1 (1st January 2019) - Chen, Zijian; Zhou, Kai; Ha, Wuzu; Chen, Peihong; Fu, Huijun; Shen, Yudong; Sun, Yuanming; Xu, Zhenlin
ABSTRACT: Melatonin (MT) is a hormone secreted by the pineal gland which regulates sleep rhythm and is widely used in health foods. However, MT is sometimes added illegally and excessively in certain health foods, which might cause undesirable side-effects. In this work, an easy-to-use immunochromatographic assay (ICA) based on mouse monoclonal antibody (mAb) for rapid detection of MT was developed for the purpose of safety. Under the optimal conditions, the developed ICA exhibited a visual limit of detection (VLOD) of 10, 000 ng/mL and a LOD of 50 ng/mL (strip reader) with the linear range from 50 ng/mL to 5000 ng/mL. Good correlation was obtained between the results of ICA and standard liquid chromatography (LC) in matrix test and blind samples test. The developed ICA can be applied for rapid detection of samples within 30 min, and is potentially an excellent tool for screening of MT in health foods. GRAPHICAL ABSTRACT: